Doxorubicin Loading on Functional Graphene as a Promising Nanocarrier Using Ternary Deep Eutectic Solvent Systems - Zainal-Abidin, Mohamad Hamdi; Hayyan, Maan; Ngoh, Gek Cheng; Wong, Won Fen (American Chemical Society, 2020)
The application of graphene in the field of drug delivery has attracted massive interest among researchers. However, the high toxicity of graphene has been a drawback for its use in drug delivery. Therefore, to enhance the biocompatibility of graphene, a new route was developed using ternary natural deep eutectic solvents (DESs) as functionalizing agents, which have the capability to incorporate various functional groups and surface modifications. Physicochemical characterization analyses, including field emission scanning electron microscope, fourier-transform infrared spectroscopy, Raman spectroscopy, Brunauer-Emmett-Teller, X-ray diffraction, and energy dispersive X-ray, were used to verify the surface modifications introduced by the functionalization process. Doxorubicin was loaded onto the DES-functionalized graphene. The results exhibited significantly improved drug entrapment efficiency (EE) and drug loading capacity (DLC) compared with pristine graphene and oxidized graphene. Compared with unfunctionalized graphene, functionalization with DES choline chloride (ChCl):sucrose:water (4:1:4) resulted in the highest drug loading capacity (EE of 51.84% and DLC of 25.92%) followed by DES ChCl:glycerol:water (1:2:1) (EE of 51.04% and DLC of 25.52%). Following doxorubicin loading, graphene damaged human breast cancer cell line (MCF-7) through the generation of intracellular reactive oxygen species (>95%) and cell cycle disruption by increase in the cell population at S phase and G2/M phase. Thus, DESs represent promising green functionalizing agents for nanodrug carriers. To the best of our knowledge, this is the first time that DES-functionalized graphene has been used as a nanocarrier for doxorubicin, illustrating the potential application of DESs as functionalizing agents in drug delivery systems. © 2020 American Chemical Society.